Incidence of associated events during the performance of invasive procedures in healthy human volunteers - Highstead, R. Grant; Tipton, Kevin D.; Creson, Daniel L.; Wolfe, Robert R.; Ferrando, Arny A. (Journal of applied physiology (1985), 2005)
Metabolic investigations often utilize arteriovenous sampling and muscle biopsy. These investigations represent some risk to the subject. We examined 369 studies performed in the General Clinical Research Center between January 1994 and May 2003 for events related to femoral catheterization and muscle biopsies. Incidents were further examined by age (younger: 18-59 yr, n=133; and older: 60-76 yr, n=28). There were no clinically defined major complications associated with either procedure. The incidence of femoral catheter repositioning or reinsertion was higher in the older group (25.5 vs. 9.7%). There was no difference in the incidence of premature removal of catheters, ecchymosis or hematoma, or the persistence of pain after discharge. The occurrence of all incidents did not increase with multiple catheterizations. Muscle biopsy was associated with infrequent ecchymosis or hematoma in both groups (1.1 and 3.6% in younger and older groups, respectively). Both procedures entail a small likelihood of a vagallike response (3.3% overall), resulting in nausea, dizziness, and rarely a loss of consciousness. These results indicate that, in skilled hands and a defined clinical setting, the incidents associated with femoral catheterization and muscle biopsy in healthy volunteers are reasonable and largely controllable.